Suppression of Nonsense Mutations by New Emerging Technologies - Pedro Morais (International Journal of Molecular Sciences, 2020)
Nonsense mutations often result from single nucleotide substitutions that change a sense codon (coding for an amino acid) to a nonsense or premature termination codon (PTC) within the coding region of a gene. The impact of nonsense mutations is two-fold: (1) the PTC-containing mRNA is degraded by a surveillance pathway called nonsense-mediated mRNA decay (NMD) and (2) protein translation stops prematurely at the PTC codon, and thus no functional full-length protein is produced. As such, nonsense mutations result in a large number of human diseases. Nonsense suppression is a strategy that aims to correct the defects of hundreds of genetic disorders and reverse disease phenotypes and conditions. While most clinical trials have been performed with small molecules, there is an increasing need for sequence-specific repair approaches that are safer and adaptable to personalized medicine. Here, we discuss recent advances in both conventional strategies as well as new technologies. Several of these will soon be tested in clinical trials as nonsense therapies, even if they still have some limitations and challenges to overcome.